Characterizing, modeling, and analyzing soft error propagation in asynchronous and synchronous digital circuits - Bany Hamad, Ghaith; Hasan, Syed Rafay; Ait Mohamed, Otmane; Savaria, Yvon (Microelectronics and reliability, 2015)
•Analysis of soft error propagation in asynchronous and synchronous digital designs.•Modeling electrical and logical masking at gate level by utilizing MDG and GP sets.•Identification of soft error propagation critical inputs sequences.•Faster, efficient, and more accurate estimation of the soft error rate (SER). Soft errors, due to cosmic radiations, are one of the major challenges for reliable VLSI designs. In this paper, we present a symbolic framework to model soft errors in both synchronous and asynchronous designs. The proposed methodology utilizes Multiway Decision Graphs (MDGs) and glitch-propagation sets (GP sets) to obtain soft error rate (SER) estimation at gate level. This work helps mitigate design for testability (DFT) issues in relation to identifying the controllable and the observable circuit nodes, when the circuit is subject to soft errors. Also, this methodology allows designers to apply radiation tolerance techniques on reduced sets of internal nodes. To demonstrate the effectiveness of our technique, several ISCAS89 sequential and combinational benchmark circuits, and multiple asynchronous handshake circuits have been analyzed. Results indicate that the proposed technique is on average 4.29 times faster than the best contemporary state-of-the-art techniques. The proposed technique is capable to exhaustively identify soft error glitch propagation paths, which are then used to estimate the SER. To the best of our knowledge, this is the first time that a decision diagram based soft error identification approach is proposed for asynchronous circuits.